Loss of SOX18/CLAUDIN5 disrupts the pulmonary endothelial barrier in ventilator-induced lung injury - Garcia-Flores, Alejandro E.; Gross, Christine M.; Zemskov, Evgeny A.; Lu, Qing; Tieu, Kim; Wang, Ting; Black, Stephen M. (Frontiers in Physiology, 2022)
Mechanical strain contributes to ventilator-induced lung injury (VILI) through multi-factorial and complex mechanisms that remain unresolved. Prevailing evidence suggests that the loss of pulmonary endothelial tight junctions (TJs) plays a critical role. TJs are dynamically regulated by physiologic and hemodynamic forces to stabilize the endothelial barrier. The transcription factor sex-determining region Y-box (SOX)-18 is important in regulating blood vessel development and vascular permeability through its ability to regulate the transcription of Claudin-5, an endothelial TJ protein. Previously, we demonstrated that SOX18 expression is increased by shear stress in the pulmonary endothelium. Therefore, in this study, we investigated how mechanical strain mediated through cyclic stretch affects the SOX18/Claudin-5 regulatory axis. Our data demonstrate that SOX18 and Claudin-5 are downregulated in human lung microvascular endothelial cells (HLMVEC) exposed to cyclic stretch and the mouse lung exposed to high tidal mechanical ventilation. Overexpression of SOX18 reduced the loss of Claudin-5 expression in HLMVEC with cyclic stretch and preserved endothelial barrier function. Additionally, overexpression of Claudin-5 in HLMVEC ameliorated barrier dysfunction in HLMVEC exposed to cyclic stretch, although SOX18 expression was not enhanced. Finally, we found that the targeted overexpression of SOX18 in the pulmonary vasculature preserved Claudin-5 expression in the lungs of mice exposed to HTV. This, in turn reduced lung vascular leak, attenuated inflammatory lung injury, and preserved lung function. Together, these data suggest that enhancing SOX18 expression may prove a useful therapy to treat patients with ventilator-induced lung injury.